Medicinal plants used in the management of cancers by residents in the Elgon Sub-Region, Uganda - Ali Kudamba; Josephine N. Kasolo; Godfrey S. Bbosa; Allan Lugaajju; Henry Wabinga; Nixon Niyonzima; Moses Ocan; Ali M. Damani; Hussein M. Kafeero; Jamilu E. Ssenku; Shaban O. Alemu; Muhammad Lubowa; et al. (BMC Complementary Medicine and Therapies, 2023)
Abstract Background In Uganda, medicinal plants have been utilized to treat a variety of ailments, including cancer. However, there is little information available about the medicinal plants used to treat cancer in the Elgon subregion. As a result, the current study documented the plant species used in the management of cancer in the Elgon sub-region. Methods Data were gathered by observation, self-administered questionnaires, interview guides, and guided field trips. Analyzing descriptive statistics and creating graphs were done using SPSS (version 21.0) and GraphPad Prism® version 9.0.0, respectively. Well-established formulae were used to calculate quantitative indices. The narratives were interpreted using major theories and hypotheses in ethnobotany. Results A total of 50 plant species from 36 families were documented, and herbal knowledge was mainly acquired through inheritance. Fabaceae and Asteraceae comprised more plant species used in herbal preparation. Most plants were collected from forest reserves (63%); herbal therapies were made from herbs (45%); and leaves were primarily decocted (43%). The most frequently used plants were Tylosema fassoglensis, Hydnora abyssinica, Azidarachata indica, Prunus Africana, Kigelia africana, Syzygium cumini, Hydnora africana, Rhoicissus tridentata, Albizia coriaria, and Plectranthus cuanneus. All the most commonly used plants exhibited a high preference ranking (60–86%) and reliability level (74.1–93.9%). Generally, the ICF for all the cancers treated by medicinal plants was close to 1 (0.84–0.95). Conclusions The ten most commonly utilized plants were favored, dependable, and most important for treating all known cancers. As a result, more investigation is required to determine their phytochemistry, toxicity, and effectiveness in both in vivo and in vitro studies. This could be a cornerstone for the pharmaceutical sector to develop new anticancer medications.